Subclinical Propionibacterium acnes infection estimation in the intervertebral disc (SPInE-ID): protocol for a prospective cohort. Issue 11 (17th November 2017) - Astur, Nelson; Martins, Delio E; Wajchenberg, Marcelo; Ferretti, Mario; Menezes, Fernando G; Doi, Andre M; Rosemberg, Laercio A; Santos, Durval C B; Iutaka, Alexandre S; Rodrigues, Luciano M R; Martino, Marines D V; Pagura, Jorge R; et al.
Abstract : Introduction: Low back pain and vertebral endplate abnormalities are common conditions within the population. Subclinical infection caused by indolent pathogens can potentially lead to these findings, with differentiation between them notably challenging from a clinical perspective. Progressive infection of the intervertebral disc has been extensively associated with increasing low back pain, with Propionibacterium acnes specifically implicated with in relation to sciatica. The main purpose of this study is to identify if the presence of an infective pathogen within the intervertebral disc is primary or is a result of intraoperative contamination, and whether this correlates to low back pain. Methods and analysis: An open prospective cohort study will be performed. Subjects included within the study will be between the ages of 18 and 65 years and have a diagnosis of lumbar disc herniation requiring open decompression surgery. Excised herniated disc fragments, muscle and ligamentum flavum samples will be collected during surgery and sent to microbiology for tissue culture and pathogen identification. Score questionnaires for pain, functionality and quality of life will be given preoperatively and at 1, 3, 6 and 12 months postoperatively. A MRI will be performed 12 months after surgery for analysis of Modic changes and baseline comparison. The primary endpoint is the rate of disc infection in patients with symptomatic degenerative disc disease. The secondary endpoints will be performance scores, Modic incidence and volume. Ethics and dissemination: This study was approved by our Institutional Review Board and was only initiated after it (CAAE 65102617.2.0000.0071). Patients agreeing to participate will sign an informed consent form before entering the study. Results will be published in a peer reviewed medical journal irrespective of study findings. If shown to be the case, this would have profound effects on the way physicians treat chronic low back pain, even impacting health costs. Trials registration number: NCT0315876; Pre-results.